Remember the Ramrods : an Army brotherhood in war and peace - Bellavia, David, 1975- (Mariner Books, 2022)
"An extraordinary re-envisioning of the scope and ambitions of the contemporary military memoir: the Iraq War's only living Medal of Honor recipient examines the bonds and wounds of war across two decades"--